China's peaceful rise : perceptions, policy and misperceptions - Herrick, Christopher W.; Subramaniam, Surain; Gai, Zheya (Manchester University Press, 2016)
Can China peacefully attain great power status in the twenty-first century? Adopting a constructivist approach, the book argues that China's prospects for achieving great power status peacefully depend more on Chinese and international perceptions of China's rise/development than on concrete measures of power or economic benefits, because power considerations and economic self-interest reflect shifting perceptions that have their roots in factors, such as historical experience and national image. Incorporating historical perceptions, survey data and general analysis, the book explores Chinese foreign policies in international organizations, international trade, security relations and as a model for global governance, plus the reactions to those policies within the context of China's relations with Asian neighbours (India, Japan and the states of South-east Asia), existing international powers (the European Union, Russia and the United States), and emergent trading partners (Africa), representing a wider number of diverse states than are included in most books.--Publisher's website.